Гераклов узел: об одном декоративном мотиве в ювелирном искусстве (на примере золотых диадем) - Малкова, Е.М. (Археологический альманах, 2010)
Статье посвящена геракловому узлу, одному из самых популярных декоративных элементов искусства Древней Греции эпохи эллинизма. Прослеживается эволюция внешнего вида и его использования в декоре золотых диадем. Гераклів вузол є одним з найбільш популярних декоративних елементів у ювелірному мистецтві античності. Найбільшого поширення він набуває за часів еллінізму. Гераклів вузол згадується практично у всіх дослідженнях, присвячених ювелірному мистецтву Давньої Греції. У роботі Р. Хіггінса (1961) мова йде про походження гераклова вузла, його використанні у декоруванні діадем. Цим же питанням приділяє увагу й М. Пфроммер (2001), на думку якого, такі вузли були дуже важливими в культурі багатьох стародавніх народів, у тому числі й у Єгипті. Heracles knot is one of the most popular decorative elements that became widely spread in the Hellenistic age. It is mentioned in almost all studies on ancient Greek jewelry, for instance, in the works by Robert Higgins and Michael Pfrommer, who consider the problem of the origin of the Heracles knot, paying special attention to its use in decorating diadems. Pfrommer said that this motif was very important in the culture of many ancient peoples, including Egyptians. Heracles knot was used in decoration of various pieces of jewelry, but mainly for diadems. This can be explained by the fact that the ancients attributed sufficiently strong protecting effect to Heracles knot. Diadem with Heracles knot, as primarily part of a female headdress, was to protect its possessor in the crucial moments of her life: during the wedding ceremony and in her preparation for future motherhood. Also, being placed in the burial, such a tiara would symbolically point to the circumstances surrounding the sacred marriage in the transition of a woman to the realm of the dead.